Tuning the sensitivity of lanthanide-activated NIR nanothermometers in the biological windows. Issue 5 (19th January 2018) - Cortelletti, P.; Skripka, A.; Facciotti, C.; Pedroni, M.; Caputo, G.; Pinna, N.; Quintanilla, M.; Benayas, A.; Vetrone, F.; Speghini, A.
Abstract : Lanthanide-activated SrF2 nanoparticles with a multishell architecture were investigated as optical thermometers in the biological windows. Abstract : Lanthanide-activated SrF2 nanoparticles with a multishell architecture were investigated as optical thermometers in the biological windows. A ratiometric approach based on the relative changes in the intensities of different lanthanide (Nd 3+ and Yb 3+ ) NIR emissions was applied to investigate the thermometric properties of the nanoparticles. It was found that an appropriate doping with Er 3+ ions can increase the thermometric properties of the Nd 3+ –Yb 3+ coupled systems. In addition, a core containing Yb 3+ and Tm 3+ can generate light in the visible and UV regions upon near-infrared (NIR) laser excitation at 980 nm. The multishell structure combined with the rational choice of dopants proves to be particularly important to control and enhance the performance of nanoparticles as NIR nanothermometers.